Identifikasi dan Analisis Galaktomanan dari Bungkil Sawit sebagai Bahan Baku Biomaterial dengan Metode FTIR dan NMR - Yogananda, Amrina Amalia; Alfian, Muhammad; Faizah, Nurul; Cahyani , Anggun Cita; Yulianti, Selvia; Irawan , Hisba Cahyani; Saputro, Rafly Restu Dwi (Universitas Borneo Lestari, 2026)
Palm kernel meal contains polysaccharide compounds, including galactomannan, which is made up of galactose and mannose units. This study aims to extract and identify the structure of galactomannan from palm kernel meal using FTIR and NMR spectroscopy. Extraction was carried out using a hot water extraction method with a material-to-solvent ratio of 1:5 at 80°C for 60 minutes, followed by precipitation with 96% ethanol, subsequent freeze-drying, and followed by characterization through FTIR and NMR to confirm the presence of characteristic functional groups associated with galactomannan. The extraction yielded 0,77% then the FTIR spectrum revealed strong bands at 1065.67, 1032.65, and 1009.16 cm⁻¹, indicating the presence of C–O and C–O–C stretching related to glycosidic bonds—key features of the galactomannan polysaccharide structure. The 1H-NMR spectrum exhibited a distinct signal for the anomeric proton in the range of approximately 5.0–5.4 ppm, with the protons from the C2–C6 positions appearing between 3.2 and 4.1 ppm. Additionally, the 13C-NMR spectrum displayed a peak for the anomeric carbon around 102–105 ppm, along with other ring carbon peaks in the range of 60–85 ppm, which align with the structure of galactomannan. These findings confirm that palm kernel meal holds promise as a source of galactomannan for developing polysaccharide-based biomaterials